Irrigation water management in Iran: Implications for water use efficiency improvement - Nazari, Bijan; Liaghat, Abdolmajid; Akbari, Mohammad Reza; Keshavarz, Marzieh (Agricultural water management, 2018)
•Despite increasing water scarcity in Iran, irrigation water use is still inefficient.•Water management has failed due to legal, social, technological and political dynamics.•Government should revise its approach to manage weaknesses, threats and potentials.•Rethinking agriculture role in development and improving water productivity are needed.•Raising governors’ awareness about risk of populist development agendas is vital. Water is the most essential resource for the production of agricultural goods and services. However, high levels of water stress and increased frequency and intensity of droughts, which are mainly driven by climate change dynamics, have reduced the stock of freshwater resources in arid and semi-arid regions, such as Iran. Despite the major reduction of freshwater resources, the efficiency of irrigation water use has remained very low in the country and performance of water management schemes is far from satisfactory. Using the strengths, weaknesses, opportunities and threats/political, economic, social, technological, legal and environmental (SWOT/PESTLE) analysis, this paper explores 40 internal and external factors that influence irrigation water management in Iran and recognizes legal, social, technological and political dynamics as the major reasons for failure of irrigation water management in the country. A combination of the threats, opportunities, weaknesses and strengths (TOWS) matrix and bottleneck analysis was used to suggest irrigation water management strategies that rehabilitate the failed schemes and enhance water security in the agriculture sector. Rethinking the role of intensified agriculture in development along with raising the awareness and attitude of decision makers towards the risk of shortsighted water resource development plans, in addition to promoting agro-based industries and developing integrated plans to improve water efficiency are the strategies that can contribute to a more effective management of irrigation water in Iran.